ESTUDOS SÔBRE OBTENÇÃO DE LEVEDURA ALIMENTAR EM SUBSTRATOS DE VINHAÇA - Serzedello, A.; Miguel, A. P. Nuevo; Camargo, I. J. Barsante de; Barbieri, G. (REVISTA DE AGRICULTURA, 2016)
ESTUDOS SÔBRE OBTENÇÃO DE LEVEDURA ALIMENTAR EM SUBSTRATOS DE VINHAÇA